Penggubalan dan Pelaksanaan Undang-Undang Islam oleh Pemerintah: Satu Pandangan (Kanun: Jurnal Undang-undang Malaysia, 2012)
There is an urgent need for a proper interpretation and understanding of Islamic law as a term under the jurisdiction of the government in its implementation of its Siyasah Shariah. A lack of understanding of the term and its position under the jurisdiction of the goverment would invite accusations that the law implemented by the governmentas is un-Islamic. This library-researched focuses on the issue of Islamic law as a term and its relationship with the government particularly in the legislation. The findings revealed that Islamic law has its own specific meaning and it has to come under the purview of the goverment, not of the people. Nevertheless, the government has to certain minimum requirements in order to enact and enforce the law as Islamic law, and to claim compliance from the people.Keywords: Islamic law, legislation, extent of jurisdiction.